The digital servitization of machine manufacturers – key challenges of the business transformation - Lautjärvi, Riku (My University, 2019)
Machine manufacturers have made significant investments in their digital servitization efforts, but many of them have struggled to make these investments successful. The goal of this study was to define the digital servitization phenomenon, how it affects machine manufacturers’ business and to identify the key challenges that these companies are struggling with. While servitization has received a lot of attention by scholars, as has digitalization, digital servitization has not been studied sufficiently yet. Moreover, while companies are struggling with digital servitization, little research has been done on their key challenges. This study aimed to fill this research gap. The study was conducted as a qualitative case study, featuring two large machine manufacturers as the case companies. The study featured a literature review of existing servitization, digitalization and digital servitization research, and used these different fields to define digital servitization and its effects and challenges. The empirical data about the key challenges of digital servitization was collected by interviewing six various stakeholders, three from each case company. These interviewees represented the service and product businesses as well as digitalization, as these were seen as the key stakeholders in digital servitization. The findings of this study show that companies are facing many significant challenges in different areas. These challenge areas correlate with the findings of previous literature. However, compared to previous literature, the findings of this study indicate that technological challenges are not as significant as some other studies have found them to be. The biggest problems in digital servitization found in this study are related to the processes and operating models in the machine manufacturing industry. The industry is not built to support digital services and the processes and ways of working are often incompatible with the new requirements. Scattered and siloed organizational structures are also common to machine manufacturers, which is significantly hindering the development of digital services. Digitalization cuts across the entire organization, and digital service development requires that internal organizations are aligned and involved in the development in a synchronized manner. Siloed organizations can make this very difficult. Companies have to also realize that digital services should not be judged solely based on traditional KPIs such as ROI. It has to be understood that digital servitization is a long-term strategy and having unrealistic short-term goals can lead to failure. However, changing the nature of how things have been done in the past is a complicated and long process, and machine manufacturers should be prepared for that.